CONVERSION OF ¿-HALOESTERS AND ALKYNES INTO CORRESPONDING CINNAMATES AND KETONES DERIVATIVES RESPECTIVELY BY USING SOME ORGANOTELLURIUM COMPOUNDS AS REAGENTS - Fenjan, Abdel-Amir M (Al-Nahrain Journal of Science, 2018)
Telluroxidation of di-n-propyl telluride 1 guides to obtain trans - cinnamate derivatives fromcondensation of substituted aldehydes and a-haloesters in one pot reaction. p-Diphenetyltellurinic acid anhydride 3 converts terminal alkynes into corresponding ketones through hydrationprocess to oxidize triplet bond into carbonyl group. Infrared spectra have assisted allorganochemical conversions and their identification strongly. The possible reactions mechanismswere proposed.